Demographic parameters of the indigenous egg parasitoids, Trichogramma spp., parasitizing the invasive tomato leafminer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - T. N. Manohar (Egyptian Journal of Biological Pest Control, 2019)
Abstract Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), one of the most destructive pests of tomato, has recently invaded India. Before recommending any bio-control agent for its control, it is important to study the demographic parameters of the bio-agent on the pest. The present study evaluates the demographic parameters of indigenous trichogrammatids namely Trichogramma achaeae Nagaraja and Nagarkatti, T. pretiosum Riley, T. chilonis (Ishii), and T. pieridis Nagaraja and Prashanth against this pest, aiming to select the most effective egg parasitoid species. Significant differences were observed among the demographic parameters of different Trichogramma spp. Parasitization potential of a thelytokous strain of T. pretiosum was the highest, followed by T. achaeae, T. chilonis, and T. pieridis. Population growth parameters net reproductive rate, intrinsic rate of natural increase, finite rate of increase, and weekly multiplication rate were highest, and generation time and doubling period were shortest for T. pretiosum, followed by T. achaeae, T. chilonis, and T. pieridis. The study concluded that T. pretiosum could be considered a potential candidate for biological control of T. absoluta; however, field evaluation is required before final recommendation.